Republic of Estonia : Staff Report for the 2010 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Despite enduring one of the sharpest contractions in the EU, Estonia has been successful in its all-out efforts to join the euro area. Core prices have also begun increasing but at a moderate rate. Recent wage increases have defied not only high unemployment but also increases in vacancies and long-term unemployment. Executive Directors welcomed the authorities' medium-term goal of returning to budget surpluses to restore fiscal reserves and keep public debt at low levels. Directors observed that the financial sector had weathered the crisis relatively well.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet